Effect of Chicken Coccidia Vaccine and Anticoccidial Drugs Shuttle Program on the Drug Resistance of Coccidia - Qing WANG; Xianjun ZENG; Zhihong FAN; Jiana HE; Huahua KANG; Shunian HE; Jie CHEN; Xinyu PENG (Guangdong nongye kexue, 2022)
【Objective】The study was carried out to investigate the effect of biological shuttle program using coccidia vaccines and anticoccidial drugs on the drug resistance of chicken coccidia in broiler farms.【Method】Huadu isolates of Eimeria tenella were isolated and identified from five chicken farms in Huadu District, and these farms have been using coccidial vaccine and anti-coccidial drug shuttle program. Yingde isolates of E. tenella were isolated from five chicken farms in Yinde City, and the five farms have been using only anti-coccidial drugs to control coccidiosis. The resistances of Huadu and Yingde isolates to 6 anticoccidial drugs were tested respectively by using indicators including anticoccidial index (ACI), rate of reduction in lesion score (RLS), percentage of optimum anticoccidial activity (POAA) and relative oocyst production (ROP).【Result】The cecal tissue sections of chickens of the two challenged groups showed that the mucosal layer was extensively affected with loss of intestinal glands, inflammatory cell infiltration, and many coccidial oocysts were found in the mucosa and submucosa. The results of ACI showed that the Huadu isolates were resistant seriously to nicarbazine, clodipidine and maduramycin, and moderately resistant to other 3 drugs; and the Yingde isolates were moderately resistant to all 6 drugs. The results of POAA showed that the Huadu isolates were sensitive to the mixture of maduramycin and nicarbazine, but resistant to other drugs, while the Yingde isolates were sensitive to all 6 drugs. The results of RLS and ROP showed that the two mixed isolates were resistant to all 6 drugs. Based on comprehensive evaluation, the Huadu isolates were resistant moderately to mixture of maduramycin and nicarbazine, and resistant seriously to other five drugs; while the Yingde isolates were resistant moderately to all six drugs.【Conclusion】The field isolates of chicken coccidia were resistant to anticoccidial drugs at different levels with multi-drug resistances. Both isolates from Huadu District and Yingde City showed resistance to six drugs moderately or seriously, suggesting that biological shuttle program could not significantly restore sensitivity of E. tenella compared to program using anticoccidial drugs only.